Endophytic Fungi, Drechslera spicifera, Mediated Synthesis of Biogenic Silver Nanoparticles - Deore, Sharada Laxman; Baviskar, Bhushan Arun; Sonar, Preeti N; Kide, Anjali Ashokarao; Shende, Bhavana Ashokarao (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: In present communication, endophytic fungi Drechslera spicifera is isolated from leaves of Cardiospermum halicacabum and used as a reducing agent for silver nanoparticles (AgNPs) synthesis. Materials and Methods: Synthesized AgNPs were characterised using UV-vis spectroscopy, FTIR, scanning-electron microscopy (SEM) and particle size analysis. Total phenolic, flavonoid content and antioxidant potential of endophytic fungi (culture and aqueous extract), host plant Cardiospermum halicacabum (methanol and aqueous extracts) and silver nanoparticles (culture and aqueous extract mediated silver nanoparticles) was determined. Results and Conclusion: The endophytic fungi Drechslera spicifera forms stable AgNPs and also showed good antioxidant potential for pharmaceutical applications.
Keywords: Cardiospermum halicacabum; Drechslera spicifera; Endophytic fungi; Silver nanoparticle; Antioxidant